Sistem Informasi Geografis Kerusakan Jalan Poros Bulu Dua Kabupaten Soppeng Berdasarkan Nilai Pavement Condition Index (PCI) - Nur, Siska Utami; Riska; Badaron, St Fauziah; Alifuddin, Andi; Salim (Program Studi Teknik Sipil Fakultas Teknik Universitas Muslim Indonesia, 2025)
Road damage in Soppeng Regency presents a major challenge in infrastructure maintenance due to climatic factors, extreme temperatures, substandard material quality, and unstable subgrade conditions. This study aims to identify the types and severity of pavement damage on the Bulu Dua arterial road using the Pavement Condition Index (PCI) method and to visualize the analysis results through a Geographic Information System (GIS). The research method involved processing pavement damage data with PCI and mapping using GIS. The results show that along a 10 km road segment, the predominant type of damage is raveling (89.38%), followed by depression (6.94%), shoving (6.04%), patching (5.43%), alligator cracking (5.32%), potholes (1.31%), and edge cracking (0.16%). The findings indicate seven types of pavement damage were identified on the Bulu Dua Road in Soppeng Regency, with raveling as the most dominant (89.39%). Mapping using Relive identified 63 damage points, supporting more effective prioritization of road maintenance and rehabilitation.